Water absorption and leaching of a 1K structural model epoxy adhesive for the automotive industry. (January 2023) - Bruckner, Thomas Maximilian; Singewald, Tanja Denise; Gruber, Ralph; Hader-Kregl, Laura; Klotz, Michael; Müller, Mathias; Luckeneder, Gerald; Rosner, Martin; Kern, Carina; Hafner, Martina; Paulik, Christian
Abstract: In this study the leaching of a one component (1K) structural epoxy model adhesive for the automotive industry is analysed via fourier transform infrared spectroscopy (FT-IR). In addition, the gravimetric water uptake and morphological changes were observed. Results: Findings indicate a two-stage water absorption at room temperature, whereas at 70 °C the water absorption shows a drastically increased value including a loss of mass after 500 h of immersion in DI-water. Water content at ambient conditions shows a dependency of the absolute humidity. FT-IR analyses of the dried eluate originating from immersion at 23 °C reveals typical bands of the latent hardener dicyandiamide and the filler CaCO3 . On the other hand, the spectrum of the eluate originating from immersion at 70 °C exhibits bands of the fumed silica used as rheological additive. Microscopical observation by means of scanning electron microscopy (SEM) of the adhesive reveals that cavities arise in the vicinity of the inorganic particles contained in the adhesive due to water uptake. Highlights: A novel, near to realism structural epoxy adhesive for scientific purposes. Gravimetric water uptake in structural epoxy adhesive. Leaching of substances. Morphological changes upon water uptake.